Penyuluhan Penerapan Media Interaktif Untuk Analisis Leksikal Dalam Pengembangan Kosakata Bahasa Inggris - Suerni; Melati Rahma Suri; Riswan Syahputra Damanik (STIKES Columbia Asia Medan, 2024)
Vocabulary mastery is a fundamental component in English language learning that determines comprehension, speaking, and writing skills. However, in the context of district-level communities, including the Regional Library of Labuhan Batu, vocabulary learning still faces various challenges such as the lack of contextual teaching materials, the dominance of rote learning methods, and the limited use of local resources. To address these issues, this Community Service Program (PkM) proposes the application of lexical analysis on 100 local library documents as the basis for developing interactive media used in vocabulary training. The method employed is a community-based participatory approach, with stages including preparation, lexical analysis, media development, training, and evaluation. Corpus analysis produced 27,800 word types with 200 high-frequency words and 1,350 distinctive local vocabulary items. The interactive media developed include multimedia modules, Wordwall quizzes, mobile-based gamification, and bilingual infographics. The training was attended by 40 participants, with evaluation results showing a significant improvement in the average post-test score (76.8) compared to the pre-test (42.5), and 82.5% of participants achieving scores ≥70. Furthermore, 90% of participants reported increased motivation to learn, and 85% considered the locally based materials more relevant. Thus, this PkM provides a tangible contribution to enhancing English literacy through local vocabulary and offers an interactive learning model that can be replicated in other regional libraries in Indonesia.